Laxmi's Mooch - Anand, Shelly; Ali, Nabi H. (New York : Kokila, 2021)
After Laxmi's friend Zoe points out the hairs on her lip, Laxmi is very self-conscious until her East Indian parents help her to accept and celebrate her appearance.
Keywords: Mustaches -- Juvenile fiction; Beauty, Personal -- Juvenile fiction; Self-confidence -- Juvenile fiction; East Indian Americans -- Juvenile fiction; Mustaches -- Fiction; Beauty, Personal -- Fiction; Self-confidence -- Fiction; East Indian Americans -- Fiction; Picture books